Pelatihan Adaptive Marketing Strategy untuk Bisnis Kecil Menghadapi Disrupsi Teknologi - Kespandiar, Tengku; Elizabeth; Pujiastuti, Endah; Munizu, Musran; Misrofingah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The accelerated advancement of digital technology has brought about substantial disruption across multiple sectors, notably among small businesses. Numerous small enterprises encounter obstacles in sustaining their operations and remaining competitive due to shifting consumer behaviors, the proliferation of new digital platforms, and the necessity for adaptive marketing approaches. This community engagement initiative sought to strengthen the capacity of small business owners to address technological disruption by providing training in adaptive marketing strategies. The program employed interactive workshops, group discussions, and case simulations, engaging 25 micro, small, and medium enterprise (MSME) participants from diverse sectors within the target area. Training content focused on the evolving digital marketing landscape, the significance of data-driven strategies, effective use of social media, and the application of pertinent digital marketing tools.